Prevention of Violence Against Wife In The Household (Human Rights Perspective) - Margie Gladies Sopacua (SASI, 2021)
This paper aims to find and discuss new ideas or thoughts in preventing violence against wives in the household. This research is a normative legal research, the type of research is descriptive analytical.  Sources of Legal Materials used are primary legal materials and secondary legal materials. The technique of collecting legal materials is through a library research on legal materials, both primary legal materials, secondary legal materials, then analyzed qualitatively on the problems, as well as conducting an inventory and systematization. The results of this study found several new ideas in an effort to prevent before the occurrence of domestic violence, including 1) as part of a legal society we must help each other in creating a “harmonious household” 2) provide understanding to husbands that domestic violence against wives is a crime that can be subject to legal sanctions, 3) help instill good religious values for men in this case is the husband 4) Build a positive mindset for men as husbands to fight egoism and believe that violence against wives is something that is prohibited 5) The role of religious leaders in this case is every couple who is getting married must at least carry out premarital counseling for 3 (three) months, and 6) be aware that domestic violence committed to the wife will have a psychological impact that is not good for the wife, especially the child's psychology.